How Do Beliefs about the Gender Wage Gap Affect the Demand for Public Policy? - Sonja Settele (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2020)
I conduct a pre-registered online survey experiment with a representative sample of the US population to study the relationship between people's beliefs about the size of the gender wage gap and their demand for policies aimed at mitigating it. While the correlation between beliefs and policy demand is strong, the corresponding causal effect accounts for a minor share of the differences in policy demand across the political spectrum and by gender. Instead, correlational evidence suggests a larger role for deeply-rooted world views and preferences. I document that selective information acquisition may sustain individual beliefs in line with these preferences.
Keywords: C91; D63; D72; D83; J38; J78; 330; gender wag gap; beliefs; policy preferences; fairness; information experiment; incentivized beliefs; obfuscated follow-up